Periodized training achieves better autonomic modulation and aerobic performance than non-periodized training - Clemente-Suarez, V. J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of the present research was to analyze autonomic response and aerobic performance after performing three different workloads training distributions. METHODS: Thirty athletes (mean age 38.7±9.8 years, height 174.7±6.5 cm, body weight 72.0±9.8 kg) were randomly divided into three groups of 10 participants each, to perform three different 4-week training programs: in a PRO group, aerobic training intensity increased during the 4 weeks; in a UNI group, aerobic intensity was uniform throughout the program; and in a FRE group, free training was performed. Total power, the very-low-frequency band, the low-frequency (LF) band, the high-frequency (HF) band, LF and HF normalized, basal heart rate, LF/HF ratio and maximal aerobic velocity were measured before and after the 4 weeks of training. RESULTS: A significantly increase (P<0.05) in HF and HF normalized in the PRO group was measured. The basal HR of FRE group increased significantly after the 4-week training program. CONCLUSIONS: After a 4-week training, PRO training workload distribution achieved higher autonomic adaptation than UNI and FRE training workload distribution. This information could help the coaches to develop better training programs and organize correctly the different mesocycles of training during the season to obtain a correct autonomic response of their athletes.